Bio-hydrogen Production Using Modified Zeolite Decorated with Green Iron Oxide Nanoparticles During the Fermentation Process from Food Industry Wastewater - Elahe Mansouri; Mohammad Hossein Sayadi; Nazanin Fahoul (Journal of Water and Environmental Nanotechnology)
The production of biohydrogen from industrial food wastewater is feasible using innovative, and renewable methods. In particular, dark fermentation with Fe3O4/ZSM-5 catalysts and industrial food wastewater as a carbon source has been successfully implemented by bacteria. The optimization of three parameters including the concentration of Fe3O4/ZSM-5 nanoparticles, temperature, and pH were input into the software environment. It was carried out using RSM software and the Central Composite Design model.  The software was set to run 20 experiments for replicating the tests. The optimal conditions were found to be a nanoparticle concentration of 300 mg/L, a pH of 5.5, and a temperature of 36 degrees Celsius, leading to a hydrogen production efficiency of 250.8 mL. These results show that nanoparticles at specific concentrations enhance bacterial activity by affecting intracellular enzymes, thereby improving efficiency. Consequently, the green synthesis of Fe3O4/ZSM-5 nanoparticles and the dark fermentation process have great potential for biohydrogen production from industrial food wastewater.